Comment: The New ILO-Report on Child Labour - a Document of Self-Satisfaction - Philip Meade (Social Work and Society, 2006)
The Second Global Report on Child Labour presented by the International Labour Office (ILO) in May 2006 is titled:"The End of Child Labour: Within Reach". This astoundingly optimistic scenario refers to the global decline in numbers of child labourers within the past four years by 11 percent and of children in hazardous work by 26 percent. Not only scepticism is appropriate towards these numbers, they also do not pose evidence that an end of child labour could be on its way. The ILO itself expresses in its plan of action the goal to eliminate the"worst forms" of child labour, whilst for other forms of child labour no scheduled targets are set.